Application of the BEMA test for determining the level of understanding by pupils and students of the section «Electricity and magnetism» (Journal of Educational Sciences, 2020)
In this study, an attempt was made to identify whether active learning using interactive technologieshelps to improve students’ conceptual understanding of the section «Electricity and Magnetism».The study is based on testing among students in grades 10-11 of the private physics and mathematicsschool and first-year bachelors of the physics and technology faculty, educated in standard publicschools and continuing to study electromagnetism as part of the university program. A group of pupilsof a private high school, selected according to the high results of exams in natural sciences after the 7thgrade, studied in classes with good technical equipment, laboratory rooms. The educational processwas carried out with the use of active learning, accompanied by additional optional classes, in which students had the opportunity to receive additional clarification from the teacher. Since the conceptualunderstanding of the subject under study should be the basis, the foundation of the knowledge of studentswho chose the path to further study the subject and the result of studying at the school for themain course of physics, we found it acceptable to compare the results of the selected focus groups.Based on the finished test, The Brief Electricity and magnetism assessment (BEMA) is a multiple-choicetest created in 1997 by Ruth Chabey and Bruce Sherwood. This test is conducted by researchers primarilyfor introductory physics courses at college level or for advanced physics courses in high school. Thedescribed study involved 30 people from each group. This study showed that the level of conceptualunderstanding of the Electromagnetism section in both groups is low (20-22%), the use of interactivetechnologies, additional optional hours, active learning did not greatly improve the understanding ofhigh school pupils in this section, which allowed researchers to conclude at the current stage the need touse other interactive programs to better visualize processes that help to better understand the nature ofthe interaction of charged particles and electromagnetic fields. Questioning among pupils and studentsallowed us to draw preliminary conclusions about the lack of “living experience” for understanding theongoing processes. What even interactive programs – simulators do not allow to understand the essenceof the occurring phenomena in electromagnetism. Establishing a reason, identifying systematicities in theerrors in the presentation of the material would allow researchers to further change, and possibly chooseanother suitable teaching methodology for this section.Key words: BEMA, electromagnetism, interactive resources, visualization, testing, active learning,critical thinking.